The Role of Mindfulness in Reducing Academic Burnout Among University Students - Abil Fida Muhammad Qois Al Hadi, Abil Fida Muhammad Qois Al Hadi; Mahasri Shobahiya, Mahasri Shobahiya; Syahrul Adam Salleh Ibrahim, Syahrul Adam Salleh Ibrahim (Universitas Muhammadiyah Surakarta, 2025)
Academic burnout is one of the serious challenges faced by students as a result of high academic pressure, excessive workload, and complex social expectations. This study aims to explore the role of mindfulness in reducing academic burnout levels among students through a qualitative approach using a case study method. Data were collected through in-depth interviews with students who experienced burnout and applied mindfulness techniques in their academic lives. The findings reveal that mindfulness, through practices such as breathing meditation, body scan, mindful walking, and reflective journaling, is effective in reducing symptoms of emotional exhaustion, enhancing focus, and improving sleep quality and mental health. However, challenges such as time constraints, lack of consistency, and minimal environmental support hinder the implementation of these practices. Nevertheless, the participating students managed to overcome these obstacles by establishing regular practice schedules and forming support communities. This study concludes that mindfulness is an effective and adaptive strategy for managing academic burnout. Therefore, it is recommended that higher education institutions integrate mindfulness programs into counseling services, curricula, and student activities as both preventive and curative efforts to improve students’ mental well-being and academic achievement.This research is expected to serve as a foundation for the development of broader, evidence-based psychological policies and interventions in university settings